Unveiling the neurotoxicity of methylmercury in fish (Diplodus sargus) through a regional morphometric analysis of brain and swimming behavior assessment - Puga, Sónia Andreia Silva (2016)
The current study aims to shed light on the neurotoxicity of MeHg in fish (white seabream - Diplodus sargus) by the combined assessment of: (i) MeHg toxicokinetics in the brain, (ii) brain morphometry (volume and number of neurons plus glial cells in specific brain regions) and (iii) fish swimming behavior (endpoints associated with the motor performance and the fear/anxiety-like status). Fish were surveyed for all the components after 7 (E7) and 14 (E14) days of dietary exposure to MeHg (8.7 mu gg(-1)), as well as after a post-exposure period of 28 days (PE28). MeHg was accumulated in the brain of D. sargus after a short time (E7) and reached a maximum at the end of the exposure period (E14), suggesting an efficient transport of this toxicant into fish brain. Divalent inorganic Hg was also detected in fish brain along the experiment (indicating demethylation reactions), although levels were 100-200 times lower than MeHg, which pinpoints the organic counterpart as the great liable for the recorded effects. In this regard, a decreased number of cells in medial pallium and optic tectum, as well as an increased hypothalamic volume, occurred at E7. Such morphometric alterations were followed by an impairment of fish motor condition as evidenced by a decrease in the total swimming time, while the fear/anxiety-like status was not altered. Moreover, at E14 fish swam a greater distance, although no morphometric alterations were found in any of the brain areas, probably due to compensatory mechanisms. Additionally, although MeHg decreased almost two-fold in the brain during post-exposure, the levels were still high and led to a loss of cells in the optic tectum at PE28. This is an interesting result that highlights the optic tectum as particularly vulnerable to MeHg exposure in fish. Despite the morphometric alterations reported in the optic tectum at PE28, no significant changes were found in fish behavior. Globally, the effects of MeHg followed a multiphasic profile, where homeostatic mechanisms prevented circumstantially morphometric alterations in the brain and behavioral shifts. Although it has become clear the complexity of matching brain morphometric changes and behavioral shifts, motor-related alterations induced by MeHg seem to depend on a combination of disruptions in different brain regions.